Respostas

2014-04-15T13:36:00-03:00
F(x)= X2 +4x=0   a=1 b=4 c=0

(b)^2 - 4.a.c   ->16 -4 (1).(0)  Delta =16   depois

-b  + ou - Raiz quadrada de 16 ->  a=-4 b=0

Faça o mesmo na letra B 

A=1 B=-4 C=- 5

1 1 1
A melhor resposta!
2014-04-15T14:00:34-03:00
 X² +4X=0                                               
x=( -4+√4²-4·1·0)÷2

x=(-4 + 4)÷2

x=0÷2 = 0
x = -8÷2 = -4

R: ( 0, -4)

para o gráfico:
f(1)= 1² + 4×1 = 1+4 = 5    (5, 1)

f(2) = 2² + 4×2 = 4 + 8 = 12  (12, 2)


x²-4x-5 = 0
x= (-(-4) + √(-4)² - 4 ·1· (-5)  ) ÷ 2
x= (4 + √16+ 20) ÷2
x=( 4+ 6) ÷ 2
x'= 10÷2 =5
 x" = -2÷2 = -1

1 5 1